A new colour vision arrangement test to detect functional changes in diabetic macular oedema. Issue 1 (1st January 2001) - Maár, N; Tittl, M; Stur, M; Zajic, B; Reitner, A
Abstract : AIM: A study was undertaken to investigate the correlation between colour discrimination tests and the presence of macular oedema in patients with type I diabetes to find a sensitive diagnostic tool for the detection of early functional changes. METHODS: The study was performed in 39 type I diabetic patients, 10 with and 29 without macular oedema. The examination included biomicroscopy, fundus photography of the macula, videofluorescein angiography, the LogMAR visual acuity chart, Farnsworth-Lanthony desaturated D-15 test, and the new Mollon-Reffin "Minimalist" test for colour vision deficiencies version 6.0. RESULTS: A highly significant correlation was found between the tritan value of the Mollon test and the presence of clinically significant macular oedema (p<0.0015), with a high sensitivity (88.9%) and specificity (93.3%). The DD-15 test was not significant (p=0.345) and showed low sensitivity for the presence of macular oedema (36%). All variables concerning the grading of macular oedema showed a highly significant association with the tritan values of the Mollon test (p<0.0001). CONCLUSION: The results suggest that the Mollon-Reffin "Minimalist" test version 6.0 is the best colour discrimination test for detecting macular oedema, with higher specificity and sensitivity than the other methods used in the study.